2020
DOI: 10.3390/microorganisms8101528
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Response of Faecalibacterium prausnitzii to Cell-Free Supernatants from Lactic Acid Bacteria

Abstract: Interest in preventive or therapeutic strategies targeting gut microbiota is increasing. Such strategies may involve the direct replenishment of the gut microbiota with single strains or strain mixtures, or the manipulation of strain abundance through dietary intervention, including lactic acid bacteria. A few candidate species associated with health benefits have been identified, including Faecalibacterium prausnitzii. Given its growth requirements, modulation of this bacterium has not been extensively studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 57 publications
6
17
0
Order By: Relevance
“…Nevertheless, the upregulated expression of the F. prausnitzii genes involved in carbohydrate metabolism is consistent with an in-vitro study [50], which showed that carbohydrate metabolism was upregulated while DNA replication was downregulated in F. prausnitzii when expressed to cell-free supernatant of lactic acid bacteria. Although the present study did not detect any signi cant downregulation of growthrelated genes of F. prausnitzii, the lower growth rate of F. prausnitzii in the LMY sheep than in the HMY sheep suggests that the growth-related genes of F. prausnitzii were downregulated in the LMY sheep.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, the upregulated expression of the F. prausnitzii genes involved in carbohydrate metabolism is consistent with an in-vitro study [50], which showed that carbohydrate metabolism was upregulated while DNA replication was downregulated in F. prausnitzii when expressed to cell-free supernatant of lactic acid bacteria. Although the present study did not detect any signi cant downregulation of growthrelated genes of F. prausnitzii, the lower growth rate of F. prausnitzii in the LMY sheep than in the HMY sheep suggests that the growth-related genes of F. prausnitzii were downregulated in the LMY sheep.…”
Section: Discussionsupporting
confidence: 89%
“…The lactate concentration in the rumen of the LMY sheep was much higher than in the HMY sheep (~ 0.9 vs. 0.014 mM) [8]. F. prausnitzii, as shown in the present study and the study by Lebas M, et al [50], might adjust its metabolism towards carbohydrate metabolism when exposed to lactate. Its ability to utilize lactate [46] might be one plausible explanation.…”
Section: Discussionsupporting
confidence: 49%
“…Conversely, both were detected by species-specific PCR in preliminary acute ingestion assays in feces (data not shown), although these results cannot be directly extrapolated to humans. Discussing a possible explanation for the functional effect of the formulation, even with a decrease in lactobacilli relative levels, is the potential capacity of extracellular metabolites of lactic acid bacteria to act as a prebiotic for key bacteria, influencing not only their growth and cell death, but also the expression of genes related to cell protection [ 54 ]. However, it seems that changes in microbiome do not directly correlate with the strains consumed, pointing that other mechanisms not necessary based on simple colonization might have a role on the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, we observed strong divergence in the sequences upstream of the RBS. From recently published RNAseq data [20], we determined that transcription of the mam gene begins 110-bp upstream of its translational start site. This region contains a TATA box, where formation of the transcription pre-initiation complex takes place (Figure 2).…”
Section: Analysis Of the Promoter Regionsmentioning
confidence: 99%